Effectiveness of video role play with PowerPoint lecture on knowledge domain among medical students-An open label randomized control trial - Divya Ramanathan; Neethu George; Aparna Menon (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Video is an effective teaching and learning tool as it is one of the few mediums that has been used effectually in all facades of medical education both with face-to-face teaching and at a distance. During a specified amount of space and time, video description can provide more details, converting complex concepts into simpler ones. The aim of the study is to assess the effectiveness of video role play (VRP) on knowledge domain among medical students.MATERIAL AND METHODS: The study was done as an open label randomized control trial among first-year medical students in a private medical college in a rural district in Tamil Nadu, where the subjects were randomized into two groups. The intervention group was given video role-play demonstration of the specified topic with a minute description. The control group was given PowerPoint lecture of the same topic. Baseline pretest and posttest score after two weeks was done to assess the effectiveness of video role play on knowledge domain among the students.RESULTS: The mean age of the population was 18.72 (0.71) years. The gender distribution showed that 70 (47.3%) were males and 78 (52.7%) were females. The result showed that Mean ± SD score of VRP posttest [9.36 ± 0.92] was significantly more in comparison with that of post score of PowerPoint [5.16 ± 1.98].CONCLUSION: This concludes that VRP can act more effectively in understanding a lecture than using PowerPoint method. It is an interesting and exciting teaching-learning method involving the active participation of the students and the faculty.